Impact of branched‐chain amino acid supplementation on survival in patients with advanced hepatocellular carcinoma treated with sorafenib: A multicenter retrospective cohort study. Issue 10 (26th January 2016) - Imanaka, Kazuho; Ohkawa, Kazuyoshi; Tatsumi, Tomohide; Katayama, Kazuhiro; Inoue, Atsuo; Imai, Yasuharu; Oshita, Masahide; Iio, Sadaharu; Mita, Eiji; Fukui, Hiroyuki; Yamada, Akira; Nakanishi, Fumihiko; et al.
Abstract : Aim: The therapeutic efficacy of branched‐chain amino acid (BCAA) when added to sorafenib has not been fully assessed in patients with advanced hepatocellular carcinoma (HCC). This multicenter study investigated whether BCAA supplementation improves prognosis in patients with advanced HCC who underwent sorafenib treatment. Methods: This retrospective analysis included 256 patients with advanced HCC treated with sorafenib, including 55 who did and 201 who did not receive BCAA supplementation. Clinical characteristics and outcomes in relation to Child–Pugh classification were compared in the two groups. Statistical analyses of univariate, multivariate and propensity score‐based procedures were used for this study. Results: Assessment of 216 Child–Pugh A patients showed that median overall survival was significantly longer in patients with BCAA supplementation than in those without it (440 vs 299 days, P = 0.023). Multivariate analysis showed that BCAA supplementation ( P = 0.023), low α‐fetoprotein (<100 ng/mL) ( P < 0.001), less progressive Barcelona Clinic Liver Cancer stage (A and B) ( P = 0.007) and male sex ( P = 0.018) were significant independent contributors to better overall survival. The significantly longer overall survival by BCAA supplementation was verified in the analysis using the propensity score in combination with the inverse probability of treatment weighted adjustment ( P = 0.026). Assessment of the 40 Child–Pugh B patients showed no significant differences in overall survival between patients with and without BCAA supplementation. Conclusion: BCAA supplementation may be a valuable adjunctive therapy for improving prognosis in sorafenib‐treated Child–Pugh A patients with advanced HCC.